Analisis Kehilangan Minyak (Oil Losses) Pada Proses Pengolahan CPO (Crude Palm Oil) Di PT. Perkebunan Nusantara IV Kebun ADOLINA - Damanik, Rahmat Indrajaya; Zurairah, Masdania; Rezeki, Rahmad; Refiza, Refiza (Akademi Komunitas Negeri Aceh Barat, 2023)
AbstractThis study intends to evaluate the degree of oil losses in CPO processing at the